The potency of sericin as an alternative protein in collection and maturation media to support in vitro bovine oocyte maturation - Karja, N. W. K.; Satrio, F. A.; Setiyono, A.; Prasetyaningtyas, W. E.; Fahrudin, M. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
The purpose of this study was to evaluate the potency of sericin as a substitute for BSA (bovine serum albumin) to support the in vitro maturation of bovine oocytes. Cumulus-oocytes complexes were collected with BSA or 0,1% sericin, and then matured either in media with BSA or sericin. The maturation rate was evaluated based on the meiotic status of oocytes. The incidence of DNA fragmentation in oocytes was assessed by TUNEL. The percentage of oocytes reaching the MII stage in the media either with BSA or sericin was significantly higher than those of oocytes collected and matured in BSA only. Although the maturation rate of oocytes collected with BSA and then matured with sericin was comparable to oocytes in BSA-BSA groups (P>0.05) the rate was similar to oocytes collected with sericin and then even matured with BSA or sericin (P>0.05). There was no significant difference in the incidence of DNA fragmentation among the treatment groups (P>0.05), the indices of DNAfragmented oocytes were found around 17-20 %. In conclusion, Sericin has the potency to replace BSA as a source of protein either in collection media and/or in maturation media as well as potentially preventing the incidence of DNA fragmentation in oocytes.